'n Evaluering van die effektiwiteit in die gebruik van kleur- en swart-en-wit illustrasies in die ontwikkeling van retensievermoe by die opleiding van die halfgeskoolde eerstevlaktoesighouer - Lues, Liezel (Bloemfontein: Central University of Technology, Free State, 1997)
South African children, during their years at school, mostly receive education by means of a pedagogic education system. This results in the fact that on the basis of their tradition, adult learners are inclined to completely surrender their authority to their trainers during a training situation. This is in direct contradiction to the ideal class situation where mutual interaction should take place between the trainer and trainee. This inclination increases the importance of the role of the trainer and training material. Currently great development needs exist in South Africa, of which the most important is the incorporation of semi-schooled workers in the organisation. Semi-schooled workers in our country demand methods through which they can be trained in principles that will make them more productive and effective workers. The first level supervisor (semi-schooled) is responsible for the supervision of these production workers and therefore forms a niche in the labour market which is responsible for production. The above-mentioned situation led to the development of a suitable training course specifically for the semi-schooled supervisors in the organisation. The goal of this course was to provide supervisors with principles for the development of an improved labour market. This training programme, "The Winning Supervisor" , makes use of colour illustrations to optimise Human Resources Development Training. This course is aimed at first-level supervisors and supervisors who have not completed any other training programmes before. This programme has been used extensively in occupational and governmental institutions throughout South Africa. The goal of this study was to determine if the influence of colour illustrations would make a significant difference on the retention capabilities of semi-schooled first-level supervisors over the short and long term in contrast with black-and-white illustrations. Results generated from this study throws light on the composition of similar courses in order to optimise the course as an effective training programme for first-level supervIsors. Two randomly selected respondent groups (an experimental group and a control group) were identified. The experimental group (n=ll) received instruction by means of colour illustrations in the first module of The Winning Supervisor. The control group (n=lO) received instruction in the same module, but use was made of blackand- white illustrations. Both groups were tested (interviewed) immediately after exposure to the illustrations. The same measuring instrument was repeated after four weeks. The results indicated that there was no significant difference (p=O.834) in the retention capabilities on the short term between the experimental group (colour) and the control group (black-and-white) in the immediate post-test. The delayed post-test showed a significant difference between the experimental group and the control group after four weeks (p=O.046). The colour illustrations resulted in an improved retention capability on the long term ( t = -2.14 ).
Thesis
Keywords: Memory - Retention; Color - Study and teaching; Visual perception; Occupational training